2011
DOI: 10.1093/anatox/35.7.512
|View full text |Cite
|
Sign up to set email alerts
|

A Fatality Due to an Accidental Methadone Substitution in a Dental Cocktail

Abstract: A 6-year-old male child was scheduled for a dental procedure requiring conscious sedation. Prior to the procedure, the child was administered a dental cocktail containing chloral hydrate, hydroxyzine, and methadone. After returning from the dentist, the child appeared groggy and was allowed to sleep. A few hours later, he was found unresponsive, and following resuscitation attempts at a local medical center, he was pronounced dead. Toxicological analyses of femoral blood indicated the presence of hydroxyzine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While death of a patient with history of asthma has been reported [16], another patient with mild asthma was treated safely using CH with single dose of 65 mg/kg [9]; thus, asthma itself cannot be a major factor of patient death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While death of a patient with history of asthma has been reported [16], another patient with mild asthma was treated safely using CH with single dose of 65 mg/kg [9]; thus, asthma itself cannot be a major factor of patient death.…”
Section: Resultsmentioning
confidence: 99%
“…Year of publication Type of study Topic Grissinger M [8] 2019 Review Death Abdulhamid I [9] 2016 Open-label study Safety related to systemic condition Huang A [10] 2015 Comparative study Safety Nordt SP [11] 2014 Case report Death, safety McCormack L [12] 2014 Nonrandomized cohort study Safety Kang J [13] 2012 Retrospective study Safety related to systemic condition Chicka MC [14] 2012 Review Death, safety Costa LR [15] 2012 Comparative study Safety Kupiec TC [16] 2011 Case report Death de Rezende GP [17] 2007 Case report Safety Martinez D [18] 2006 Prospective, pilot study Safety Park MK [19] 2006 Prospective randomized study Safety Myers GR [20] 2004 Randomized double-blind crossover study Safety Lee JH [21] 2002 Cross sectional study Safety Leelataweedwud P [22] 2001 Retrospective study Safety Dallman JA [23] 2001 Clinical trial Safety Jung JH [24] 2001 Cross sectional study Safety Avalos-Arenas V [25] 1998 Clinical trial Safety Engelhart DA [26] 1998 Case report Death McCann W [27] 1996 Clinical trial Safety Needleman HL [28] 1995 Retrospective study Safety Sams DR [29] 1993 Case controlled study Safety Wilson S [30] 1990 Clinical trial Safety Mueller WA [31] 1985 Data collection Safety significant adverse events during or after dental treatment under sedation, including death.…”
Section: First Authormentioning
confidence: 99%
“…Finally, 37 publications reporting a total of 71 fatalities were included in the study. A total of 20 publications were case reports [9,10,12,13,18,20,22,[24][25][26][28][29][30][31][32][33][34][35][36][37], 5 were retrospective studies [6,14,21], and 12 were case studies [7,8,11,17,19,23,26,[38][39][40][41][42].…”
Section: Pubmed Publications In Totalmentioning
confidence: 99%
“…Adverse events in a health care setting have also resulted in fatal outcomes in children. A threeyear-old boy with sickle cell disease died in hospital of a morphine overdose as a result of the incorrect programming of a morphine pump (12), while a six-year-old boy died of acute methadone toxicity when the opioid was accidentally substituted for meperidine in a dental cocktail used for conscious sedation of patients (13).…”
Section: Accidental Opioid-related Deathsmentioning
confidence: 99%
“…They are commonly prescribed in developed countries for a number of indications (e.g., analgesia, addiction treatment, cough suppression) and their consumption has been increasing dramatically worldwide, more than tripling between 1991 and 2010 (8). This class of drugs is of interest to those investigating pediatric deaths for a number of reasons: rates of opioid use in children for treatment of chronic pain are increasing in North America (9, 10); it has been shown that opioids are frequently implicated in poisoning deaths of young children (3,11); their prevalence increases the risk of both intentional and accidental administration in children (9); it has been estimated that codeine, methadone, hydrocodone and morphine could be fatal in toddlers with as little as a single dose (11); pediatric fatalities from iatrogenic medication errors have been reported (12,13); and many opioid drugs cross the placenta and are excreted in breast milk, resulting in potential exposure of the fetus and neonate (7,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%